Pengaruh Pelatihan Diversifikasi Produk terhadap Pengembangan Industri Usaha Tape di Banjarsari - Prasetyo, Abdul Rahman; Kusumaningrum, Shirly Rizki; Wulandari, Dwi; Aruna, Alby; Marcelliantika, Adinda; Surya, Eka Putri; Rahmawati, Nila (VISA: Journal of Vision and Ideas, 2024)
The tape business industry in Banjarsari Village faces challenges in increasing competitiveness through product diversification. The main objectives include identifying gaps in producer knowledge, improving the quality of tape products, and supporting downstream policies. The methods applied are Objective-Oriented Project Planning (OPP) and Logical Framework Approach (LFA), with a focus on analyzing skills needs and product quality standards. The research location is in Banjarsari Village with the main target being tape producers. The results show a significant increase in producers' knowledge and skills after the training, as well as product quality that meets downstream standards. The benefits obtained include increasing the competitiveness of the local tape industry, support for product downstream policies, and increasing producer income. In conclusion, product diversification training has proven effective in developing the tape business industry in Banjarsari Village.